Allosteric regulation of noncoding RNA function by microRNAs. Issue 11 (1st June 2022) - Gorbea, Carlos; Elhakiem, Abdalla; Cazalla, Demián
Abstract: HSUR1 and HSUR2, two noncoding RNAs expressed by the oncogenic Herpesvirus saimiri, bind host microRNAs miR-142-3p, miR-16, and miR-27 with different purposes. While binding of miR-27 to HSUR1 triggers the degradation of the microRNA, miR-16 is tethered by HSUR2 to target host mRNAs to repress their expression. Here we show that the interaction with miR-142-3p is required for the activity of both HSURs. Coimmunoprecipitation experiments revealed that miR-142-3p allosterically regulates the binding of miR-27 and miR-16 to HSUR1 and HSUR2, respectively. The binding of two different miRNAs to each HSUR is not cooperative. HSURs can be engineered to be regulated by other miRNAs, indicating that the identity of the binding miRNA is not important for HSUR regulation. Our results uncover a mechanism for allosteric regulation of noncoding RNA function and a previously unappreciated way in which microRNAs can regulate gene expression.